Development and validation of the Cirrhotic Ascites Severity model—A patient‐reported outcome‐based model to predict 1‐year mortality - Rasmus Hvidbjerg Gantzel; Niels Kristian Aagaard; Hendrik Vilstrup; Hugh Watson; Henning Grønbæk; Peter Jepsen (Hepatology Communications, 2022)
Abstract Ascites formation is a sign of decompensation of cirrhosis and heralds a poor prognosis. The widely used standard binary classification of ascites as diuretic‐responsive or refractory does not cover the spectrum of ascites and has limited prognostic information. We developed the Cirrhotic Ascites Severity (CIRAS) model to predict 1‐year mortality among 465 patients randomized to placebo in the satavaptan trials investigating treatment of cirrhotic ascites. We used multivariable logistic regression to derive the CIRAS model based on these variables: ascites discomfort score (≤50 or >50), plasma sodium (≥140, 133–139, 125–132, or <125 mmoL/L), and a composite of ascites accumulation and diuretic treatment. We validated the prediction model in 697 trial participants randomized to satavaptan treatment. The 1‐year all‐cause mortality was 19.6%. The area under the receiver operator curve was higher for the CIRAS model than for the standard ascites classification into refractory and diuretic‐responsive in both the development cohort (0.68 [95% confidence interval (CI): 0.62–0.75] vs. 0.62 [0.57–0.68]), and the validation cohort (0.68 [0.64–0.72] vs. 0.55 [0.51–0.60]). The CIRAS model had similar discrimination to the Child‐Pugh score and nearly as good as the Model for End‐Stage Liver Disease (MELD), MELD‐Na, and MELD 3.0. Conclusions: The CIRAS model based on simple ascites‐relevant data is an easily applicable and patient‐centered way to describe the severity and prognosis of all ascites grades. It carries more prognostic information than today's label of “refractory ascites” and forms the basis for earlier and better clinical decisions related to ascites management.